Study of serum C-reactive protein concentration in cardiac failure. Issue 4 (April 1990) - Pye, M; Rae, A P; Cobbe, S M
Abstract : The serum concentration of C-reactive protein was prospectively assessed in 37 patients with various degrees of heart failure. The serum concentration of C-reactive protein was higher than normal in 26 (70%) patients. The concentration was directly related to the severity of heart failure and the stage of decompensation. Hepatic cell damage is the most likely stimulus to cytokine production and hence release of C-reactive protein in heart failure. Heart failure is an additional cause of raised serum concentration of C-reactive protein but the pathological importance of this feature is not yet known.